A novel highly efficient and accurate electrochemical detection of poisonous inorganic Arsenic (III) ions in water and human blood serum samples based on SrTiO3/β-cyclodextrin composite. (April 2019) - Karthika, A.; Selvarajan, S.; Karuppasamy, P.; Suganthi, A.; Rajarajan, M.
Abstract: Strontiumtitaniumtrioxide (SrTiO3 ) decorated β-cyclodextrin (β-CD) nanocomposite modified glassy carbon electrode was developed for the efficient and accurate determination of poisonous Arsenic (III) ions in water and blood serum samples. The synthesized SrTiO3 /β-CD nanocomposite was successfully characterized by spectral and electrochemical methods. The present SrTiO3 /β-CD nanocomposite modified GC electrode was provided an excellent electrochemical performance due to higher surface area, comparable to glassy carbon electrode with SrTiO3 and β-CD separately. The fabricated electrochemical sensor (SrTiO3 /β-CD/GCE) was showed a sensitive electrochemical response for the oxidation of Arsenic (III) in 0.1 PBS. The oxidation peak current of Arsenic (III) was obtained by Amperometric, under the optimized conditions, which linearly increased with increase the concentration of the range between 10 and 140 μM and the detection limit was found to be 0.02 μM. The present SrTiO3 /β-CD/GC electrode was also showed better stability, good sensitivity and reproducibility and is applied successfully for the detection of Arsenic (III) in water and serum samples. Graphical abstract: Image 1 Highlights: SrTiO3 /β-CD was synthesized using sono-chemical method. The lowest detection limit was found using SrTiO3 /β-CD nanocomposite modified GC electrode. The present modified electrode system may be used for the detection of the presence Arsenic (III) in water and blood serum samples.